Avaliação do desempenho de uma bomba centrífuga operando com fluidos supercríticos - Cubas, Jhoan Miguel Cubas (2024)
Although the transportation and reinjection of supercritical CO2 are not new topics, studies in the open literature on centrifugal pumps operating with supercritical fluids are rare, with limited information and, above all, do not offer methodologies to evaluate the performance of these pumps. In this context, this work presents a numerical and experimental study to evaluate the performance of a nine-stage centrifugal pump operating with supercritical fluids. A methodology is proposed to estimating the main performance parameters and the temperature when pumping these fluids, using performance information for water as a starting point. As a part of the proposed methodology, an algebraic model was developed to calculate the fluid’s temperature gain. The numerical modeling is based on the methodology implemented in the computational fluid dynamics (CFD) program ANSYS® CFX®. The variation in the thermo-physical properties of the fluid in the numerical simulations was calculated using interpolations on a thermodynamic table obtained from the REFPROP® program and coupled to the numerical model. For the experimental study, two experimental lop were used to collect torque, rotation speed, pressure rise and temperature data from the test pump operating with water and supercritical CO2. This study provided an important source of experimental data for validating the results of the numerical model and the proposed methodology. The numerical results proved to be consistent with the experimental results. With the numerical model validated, other supercritical fluid scenarios that were difficult to evaluate experimentally were explored. The analysis of numerical and experimental results showed that the affinity laws for liquids can be extended to supercritical fluids. The results also showed that the proposed methodology adequately estimates the power, pressure and temperature increase of centrifugal pumps operating with supercritical fluids. Finally, from a performance point of view, it was confirmed that centrifugal pumps are capable of pumping supercritical fluids satisfactorily. However, unlike pumping liquids, pumping supercritical fluids produces considerable temperature increases, which must be taken into account. It is expected that the approaches considered and the results discussed in this study will contribute to the scarce literature on the subject.